Toward achieving sustainable development agenda: Nexus between agriculture, trade openness, and oil rents in Nigeria - Festus Fatai Adedoyin; Olawumi A. Osundina; Festus Victor Bekun; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
Over the years, agriculture has been considered as a panacea for long-term economic growth as believed by the physiocracy school of thought. Aligning this with the United Nations' Sustainable Development Goals (specifically UN-SDG-2 which highlights zero hunger), the present study empirically complements existing studies by exploring the interactions between agriculture, trade openness and oil rents using annual time frequency series data from 1981- 2017. A series of analysis is conducted. First, a battery of non-stationarity and stationarity unit root tests are performed; these range from the traditional Augmented Dickey-Fuller (ADF) and Phillips Perron (PP) techniques to the relatively recent Zivot Andrews (ZA) unit root test which accounts for a single structural break to ascertain stationarity properties in the variables under review. Subsequently, the recent Bayer and Hanck (2013) test in conjunction with the Johansen co-integration test were used for the co-integration analysis. Furthermore, to detect the direction of causality, the Toda-Yamamoto Granger Causality test alongside the impulse response function technique shows insightful outcomes. From the empirical results, co-integration is apparent and a long-run equilibrium relationship is traced between the outlined variables over the investigated period. The causality results and impulse response analysis highlight the existence of one-way causality links running from agriculture to trade and from trade to oil rents. These are revealing given the dwindling oil market prices. More insights are elucidated in the conclusion section accordingly.
Keywords: Q10; O13; C32; C33; 330; Agriculture; sustainability; Bayer-Hanck cointegration; Nigeria